Bundling biodiversity - Geoffrey Heal (Fondazione Eni Enrico Mattei (FEEM), 2002)
Biodiversity provides essential services to human societies. Many of these services are provided as public goods, so that they will typically be underprovided both by market mechanisms (because of the impossibility of excluding non-payers from using the services) and by government-run systems (because of the free rider problem). I suggest here that in some cases the public goods provided by biodiversity conservation can be bundled with private goods and their value to consumers captured in the price realized by the private goods. This may lead to an efficient level of provision.
Keywords: H41; Q2; R41; 330; Local public goods; bundling; price discrimination; monopoly; environment; urban development; Artenvielfalt; Lokale öffentliche Güter; Preisdifferenzierung; Willingness to pay; Theorie; Südliches Afrika